The Facilitative Effect of Transcranial Direct Current Stimulation on Visuospatial Working Memory in Patients with Diabetic Polyneuropathy: A Pre–post Sham-Controlled Study - Wu, Yi-Jen; Tseng, Philip; Huang, Han-Wei; Hu, Jon-Fan; Juan, Chi-Hung; Hsu, Kuei-Sen; Lin, Chou-Ching (Frontiers in Human Neuroscience, 2016)
Diabetes mellitus (DM) can lead to diabetic polyneuropathy (DPN) and cognitive deficits that manifest as peripheral and central neuropathy, respectively. In this study we investigated the relationship between visuospatial working memory (VSWM) capacity and DPN severity, and attempted to improve VSWM in DPN patients via the use of transcranial direct current stimulation (tDCS). Sixteen DPN patients and sixteen age- and education-matched healthy control subjects received Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV) and Montreal Cognitive Assessment (MOCA) for baseline cognitive assessment. A forward- and backward-recall computerized Corsi block tapping task (CBT), both with and without a concurrent motor interference task was used to measure VSWM capacity. Each DPN patient underwent a pre-treatment CBT, followed by tDCS or sham treatment, then a post-treatment CBT on two separate days. We found that although patients with severe DPN (Dyck’s grade 2a or 2b) showed comparable general intelligence scores on WAIS-IV as their age- and education-matched healthy counterparts, they nonetheless showed mild cognitive impairment on MOCA and working memory deficit on digit-span test of WAIS-IV. Furthermore, patients’ peripheral nerve conduction velocity (NCV) was positively correlated with their VSWM span in the most difficult CBT condition that involved backward-recall with motor interference such that patients with worse NCV also had lower VSWM span. Most importantly, anodal tDCS over the right DLPFC was able to improve low-performing patients’ VSWM span to be on par with the high-performers, thereby eliminating the correlation between NCV and VSWM. In summary, these findings suggest that 1) mild cognitive impairment and severe peripheral neuropathy can coexist with unequal severity in diabetic patients, 2) the positive correlation of VSWM and NCV suggests a link between peripheral and central neuropathies and 3) anodal tDCS over the right DLPFC can improve DPN patients’ VSWM, particularly for the low-performing patients.